Pengembangan Bahan Ajar KBC Berbasis Pembelajaran 4C Akidah Akhlak Kelas III MIT Berkah Palangka Raya - Muhammad Syabrina; Aufa Dalila; Aufi Dalila; Fitria Arini; Rabiatul Adawiyah (INDO PUBLISHING, 2026)
In the era of the industrial revolution 4.0, teaching materials need to be adapted to technological developments so that students can be interested. The type of teaching material that can attract students' interest is teaching materials in the form of interactive media. This study aims to develop digital teaching materials in the form of interactive learning media that can be used by students in grade III in learning Akidah Akhlak. This study follows the ADDIE model with five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews, observations, documentation, and questionnaires. The results of the questionnaire from material experts, design and field trials showed that this interactive learning media was very appropriate, with a percentage score reaching 93.2% including the